Procedure-Specific Thromboprophylaxis in Urological Surgeries: A Narrative Review - Shakiba, Behnam; Faegh, Ali; Emami, Sepideh; Heidari, Kazem; Maghsoudi, Robab (Urology Journal, 2024)
Purpose: Postoperative pulmonary embolism is a leading cause of mortality in patients undergoing major urologic surgeries, presenting a complex challenge in balancing the risks of venous thromboembolism (VTE) and perioperative bleeding. This study examines the current evidence on thromboprophylaxis in urological procedures, focusing on procedure-specific considerations. Methods: Literature on thromboprophylaxis in urological procedures was reviewed during the past decade. Results: Various mechanical thromboprophylaxis methods, such as compression stockings, pneumatic compression devices, foot pumps, mobilization, and exercises, are available preventive measures. Additionally, unfractionated heparin (UFH) and low molecular weight heparin (LMWH) are commonly used pharmacological agents for VTE prevention, with the choice between mechanical, pharmacological, or combined approaches tailored to individual patient characteristics and surgical requirements. Patient risk stratification into low, medium, and highrisk categories based on age, BMI, and VTE history guides the selection of thromboprophylaxis strategies. Surgical procedures are categorized as oncological or non-oncological, with uro-oncological surgeries posing a higher VTE risk than non-oncological procedures. Consequently, a combination of pharmacological and mechanical prophylaxis is typically recommended for uro-oncological patients, while pharmacological prophylaxis is reserved for high-risk individuals undergoing non-oncological surgeries. Mechanical prophylaxis is advised for high-risk patients undergoing procedures with elevated VTE risk. Conclusion: This study summarized an optimal thromboprophylaxis protocol taking into account patient risk factors and the specific urological procedure.